Laparoscopic management of acute appendicitis during pregnancy (Revista Argentina de Cirugía, 2022)
Objective: analyze the experience in diagnosis and laparoscopic treatment in acute appendicitis during pregnancy.Place of application: University HospitalDesign: retrospective analysis of a prospective database.Population: twenty six pregnant females with acute appendicitis.Method: retrospective analysis of pregnant females submitted for surgical evaluation due to clinical presumption of an acute appendicitis in the period between September 2005 and January 2013. Analysis was performed over a prospective database where demographics, associated comorbidities, and pregnancy details were stated. Characteristics of clinical presentation, time of evolution, pre-surgical exams, type of surgery performed,length of stay,pathology reports and post surgical complications, were also analyzed.Results: twenty six female patients with a mean gestational length of 18,04 weeks, were approached by laparoscopy due to acute appendicitis. Two procedures were converted. All of them confirmed the acute episode and was reconfirmed by pathology. Four patients (15,38%) had a gangrenous and perforated appendix. Surgical mean time was 73 minutes with a mean hospital stay of 2,3 (1-6) days. One post operative complication was reported, and managed with antibiotics as an out patient. There were no reoperations or readmissions. All newborns had an adequate weight at birth. Conclusions: in our experience the laparoscopic approach is useful and safe for the mother and child with minimum morbidity and no mortality.
Keywords: appendicitis; laparoscopy; appendectomy; pregnancy